Standardised Sonneratia apetala Buch.-Ham. fruit extract inhibits human neutrophil elastase and attenuates elastase-induced lung injury in mice - Sengupta, Sayantan; Abhinav, Nipun; Singh, Sabita; Dutta, Joytri; Mabalirajan, Ulaganathan; Kaliyamurthy, Karthigeyan; Mukherjee, Pulok Kumar; Jaisankar, Parasuraman; Bandyopadhyay, Arun (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) along with asthma is a major and increasing global health problem. Smoking contributes to about 80%–90% of total COPD cases in the world. COPD leads to the narrowing of small airways and destruction of lung tissue leading to emphysema primarily caused by neutrophil elastase. Neutrophil elastase plays an important role in disease progression in COPD patients and has emerged as an important target for drug discovery. Sonneratia apetala Buch.-Ham. is a mangrove plant belonging to family Sonneratiaceae. It is widely found in the Sundarban regions of India. While the fruits of this plant have antibacterial, antifungal, antioxidant and astringent activities, fruit and leaf extracts have been shown to reduce the symptoms of asthma and cough. The aim of this study is to find whether hydro alcoholic fruit extracts of S. apetala inhibit neutrophil elastase and thus prevent the progression of neutrophil elastase-driven lung emphysema. The hydroalcoholic extract, ethanol: water (90:10), of the S. apetala Buch.-Ham. fresh fruits (SAM) were used for neutrophil elastase enzyme kinetic assay and IC50 of the extract was determined. The novel HPLC method has been developed and the extract was standardized with gallic acid and ellagic acid as standards. The extract was further subjected to LC-MS2 profiling to identify key phytochemicals. The standardized SAM extract contains 53 μg/mg of gallic acid and 95 μg/mg of ellagic acid, based on the HPLC calibration curve. SAM also reversed the elastase-induced morphological change of human epithelial cells and prevented the release of ICAM-1 in vitro and an MTT assay was conducted to assess the viability. Further, 10 mg/kg SAM had reduced alveolar collapse induced by neutrophil elastase in the mice model. Thus, in this study, we reported for the first time that S. apetala fruit extract has the potential to inhibit human neutrophil elastase in vitro and in vivo.